Parasites of the indigenous domestic fowl (Gallus gallus domesticus) in Selangor - Abdullah Sani, Rehana; M., Harisah; Y., Bohari (Persatuan Doktor Veterinar Malaysia, 1986)

(untitled)
Twenty two flocks of the indigenous domestic fowl (Gallus gallus domesticus)in Sungei Besi, Serdang and Ulu Langat were studied for parasites. Faecal examinations showed coccidia oocysts and helminth eggs belonging to cestodes, Capillaria, Strongyloides, Syngamus, Heterakis, Acuaria, Ascaridia and Oxyspirura species. The nematodes recovered from necropsied birds were Heterakis gallinae, Capillaria sp., Ascaridia galli, Capillaria annulata, Syngamus trachea, Tetrameres fissispina, Gongylonema ingluvicola and Oxyspirura mansoni. The cestodes recovered were Raillietina tetragona, Amoebotaenia sphenoides, Raillietina cesticillus and Choanotaenia infundibulum. From blood examinations, the haemoprotozoa, Leucocytozoon sabrazesi, Leucocytozoon caulleryi, Plasmodium gallinaceum and Trypanosoma sp. were observed while external body examination revealed the ectoparasites Menopon gallinae, Lipeurus caponis, Goniodes dissimilis, Goniocotes gallinae and Megninia cubitalis. No apparent gross pathogenic effects of these parasites on their host were observed